(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
The motivation for sports activity is a critical component of students’ overall well-being and academic success. This article explores the pedagogical and psychological aspects of fostering motivation for physical activities among students. By analyzing key factors influencing motivation, including intrinsic and extrinsic motivation, as well as the role of educators and the learning environment, the article aims to highlight effective methods for increasing students’ engagement in sports activities. The findings emphasize the importance of tailored strategies in developing long-lasting motivation and healthy habits in students.